ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL KESEBANGUNAN BERDASARKAN PROSEDUR NEWMAN DITINJAU DARI KEMAMPUAN SPASIAL (Penelitian dilaksanakan di Kelas IX SMPN 1 Paguyangan Kabupaten Brebes) - Widodo, An Nur Ami; Sujadi, Imam; Mardiyana, Mardiyana (Journal of Mathematics and Mathematics Education, 2017)
Abstract : The aim of this research was to identify the types of students error at 9th grade of SMPN 1 Paguyangan in solving similarity by using Newmanâs error analysis procedure from spatial ability. The type of this research is a qualitative research. Subjectâs selection procedure was by using purposive sampling. There are 6 subjects in this research. Data collection technique was task-based interviews. The validity was determined by time triangulation. The data analysis was Miles and Huberman model including reduction, data displays, and conclusion. The results of this research showed as follows. The types students with low spatial ability error in solving based on Newmanâs error analysis procedure were: reading error, comprehension error, transformation error, process skill error, and encoding errors. The types students with medium spatial ability error in solving based on Newmanâs error analysis procedure were: transformation error, process skill error, and encoding error. The types students with high spatial ability error in solving based on Newmanâs error analysis procedure were : transformation error.Keywords: types of error, Newman procedure, spatial ability.